Steroidal saponin concentrations in Brachiaria decumbens and B. brizantha at different developmental stages - Brum,Karine Bonucielli (2009)
Brachiaria species contain steroidal saponins and are involved in outbreaks of hepatogenous photosensitization. This research presents the levels of a steroidal saponin, protodioscin, in the seeds and aerial parts of B. brizantha and B. decumbens during different developmental stages (growth, bloom, fructification and seed fall). The butanolic fraction of the ethanolic extract of each stage was submitted to thin layer chromatography (TLC) and spectrophotometric analysis through the Ehrlich reagent in 515nm. The chromatograms in TLC of the butanolic fraction of B. brizantha and B. decumbens showed similar spots as the protodioscin standard. The estimated level of protodioscin isomers in B. brizantha and B. decumbens ranged from 0.5% to 2.1%, having the highest level at the end of their developmental stages during seed falling comparison with the previous one. Protodioscin was not detected in the seeds. Outbreaks of Brachiaria spp. poisoning in central Western Brazil are frequently observed in pastures that had been more than 30 days without animals grazing, and also during the growing or blooming stage of the pastures. Other saponin determinations in toxic and non toxic pastures are necessary to determine the saponin concentrations that cause intoxication.